Talking Tots and the Terrible Twos: Early Language and Disruptive Behavior in Toddlers. Issue 9 (December 2018) - Roberts, Megan Y.; Curtis, Philip; Estabrook, Ryne; Norton, Elizabeth S.; Davis, Matthew M.; Burns, James; Briggs-Gowan, Margaret; Petitclerc, Amelie; Wakschlag, Lauren S.
ABSTRACT: Objective: The goal of this article is to investigate the association between the 2 most commonly reported parental concerns about young children—disruptive behavior (e.g., irritable, aggressive, and noncompliant behaviors) and language delay in toddlers. To test for salient subgroup differences, individual differences by the sex of the child and family poverty status were examined. Methods: Participants included 1259 mothers of children between 18 and 36 months of age. Mothers completed questions about their child's language development and disruptive behavior. Information regarding poverty status as well as child age and sex were also collected. Results: Stronger language skills were associated with fewer disruptive behaviors for children between 18 and 36 months of age. This negative association was stronger for females than for males ( b = −0.243; t [1251] = −3.555; p < 0.001) and stronger for children living in poverty than for those above the poverty line ( b = −2.04; t [1251] = −2.531; p = 0.011). Conclusion: Findings from our study suggest a developmental co-occurrence pattern that begins at a very early age. Individual differences suggest that there is substantial heterogeneity in these patterns; longitudinal investigation is needed to uncover causal pathways and underlying mechanisms. Awareness of the association between these 2 developmental domains, about which parents frequently express concerns, is critical to maximizing early detection and intervention. Abstract : Supplemental Digital Content is Available in the Text.